PENGARUH PERCEIVED USEFULNESS, PERCEIVED EASE OF USE DAN PENGGUNAAN SOFTWARE AUDIT PADA KINERJA AUDITOR INTERNAL - Krisna Dewi, Ni Luh Gede; Mertha, Made (E-Jurnal Akuntansi, 2016)
The purpose of this study was to analyze the effect of perceived usefulness , perceived ease of use and the use of a software audit on the performance of internal auditors at. Bank BRI Branch Office Se Bali Province . This research was conducted at PT . Bank BRI Branch Office Se Bali Province with twelve offices in 2016 with the number of auditors as many as 50 people as samples through the method of sample saturated . The data collection is done by distributing questionnaires to 46 respondents back and four aborted through multiple linear regression analysis . Based on the analysis , perceived usefulness , perceived ease of use and the use of audit software has a positive influence on the performance of internal auditors at. Bank BRI Branch Office Se Bali Province.
Keywords: perceived usefulness, perceived ease of use, the use of software audit and internal auditor performance.